Facial twitching: calcium or concussion conundrum? Hypocalcaemia in a young American football player masking an internal carotid artery dissection. Issue 4 (28th April 2020) - Muthalagappan, Seethalakshmi; Robbins, Timothy; Mehta, Hiten; Murthy, Narasimha
Abstract : A 30-year-old male American football player presented to the acute medical unit with left-hand and hemifacial spasms. History and examination revealed hemifacial spasms in keeping with seizure-like activity possibly due to symptomatic hypocalcaemia. Subsequent investigations revealed an adjusted calcium of 1.87 mmol/L and, hence, he was managed with intravenous calcium replacement. He presented two further times in a 1-month period, with subjective limb weakness, despite normal adjusted calcium. During his third admission, he developed slurred speech and a marked facial droop, with absence of power in the right upper limb. Imaging revealed acute and old infarctions in the left middle cerebral artery territory and appearances consistent with left internal carotid artery dissection. This presentation of arterial stroke is atypical but with potentially grave consequences if missed. There is limited literature on the presentation of hemifacial spasm, and its association with ischaemic or haemorrhagic stroke represents a key learning point.